Evidence for Degradation of the Chrome Yellows in Van Gogh's Sunflowers: A Study Using Noninvasive In Situ Methods and Synchrotron‐Radiation‐Based X‐ray Techniques. (20th October 2015) - Monico, Letizia; Janssens, Koen; Hendriks, Ella; Vanmeert, Frederik; Van der Snickt, Geert; Cotte, Marine; Falkenberg, Gerald; Brunetti, Brunetto Giovanni; Miliani, Costanza
Abstract: This paper presents firm evidence for the chemical alteration of chrome yellow pigments in Van Gogh's Sunflowers (Van Gogh Museum, Amsterdam). Noninvasive in situ spectroscopic analysis at several spots on the painting, combined with synchrotron‐radiation‐based X‐ray investigations of two microsamples, revealed the presence of different types of chrome yellow used by Van Gogh, including the lightfast PbCrO4 and the sulfur‐rich PbCr1− x S x O4 ( x ≈0.5) variety that is known for its high propensity to undergo photoinduced reduction. The products of this degradation process, i.e., Cr III compounds, were found at the interface between the paint and the varnish. Selected locations of the painting with the highest risk of color modification by chemical deterioration of chrome yellow are identified, thus calling for careful monitoring in the future. Abstract : Warum dunkelt Gelb? Komplementäre Analyseverfahren belegen, dass das Pigment Chromgelb durch Cr VI →Cr III ‐Reduktion dunkelt. Das Vorhandensein verschiedener Arten von Chromgelb – lichtechtes PbCrO4 und lichtempfindliches schwefelreiches PbCr1− x S x O4 ( x ≈0.5) – wird nachgewiesen, und die Bildpartien mit dem höchsten Verfärbungsrisiko werden identifiziert.